Запобіжна та профілактична діяльність слідчого під час проведення досудового розслідування як напрями удосконалення чинного КПК України - Кочура, О. О.; Kochura, O. O.; ORCID: http://orcid.org/0000-0003-0638-2911; Балац, Р. М.; Balats, R. M.; ORCID.http//orcid.org/0000-0003-2145-9593 (Науковий вісник Херсонського державного університету. Сер. : Юридичні науки. – 2018. – Вип. 5. – С. 93-96, 2018)
У статті досліджено загальні напрями профілактичної та запобіжної діяльності слідчого під час проведення досудового розслідування. Зіставлено положення чинного КПК України з КПК України I960 р. із питань про форму запобігання кримінальним правопорушенням. Сформульоване питання щодо внесення змін у чинне кримінальне процесуальне законодавство України.

The author of the article researched the general directions of preventive activity of the investigator during pre-trial investigation. The relevance of the research topic isjustified by the presence of gaps in the national criminal procedural law regulating the implementation of preventive activities of the investigating of the pre-trial investigation of the National Police of Ukraine during the investigation into criminal proceedings. It is noted that according to the provisions of Art. 23 of the Law of Ukraine “On National Police” one of the main responsibilities of police officers is the task of carrying out preventive activities aimed at preventing offenses, as well as identifying the causes and conditions conducive to the commission of criminal and administrative offenses, to use, within their competence, measures for eliminate them. At the same time, in the “Regulations on the bodies of pre-trial investigation of the National Police of Ukraine”, approved by the Order of the Ministry of Internal Affairs of Ukraine of 06.07.2017, № 577 “On the organization of the activities of the bodies of pre-trial investigation of the National Police of Ukraine”, it was stated that one of the tasks of the pre-trial investigation bodies is to identify the causes and the conditions conducive to the commission of criminal offenses, and the use of measures to eliminate them through the appropriate authorities. The analysis of the views of the scholars of proceduralists on the above-mentioned questions, and their suggestions on the necessity to include the reasons and conditions that contributed to the commission of criminal offenses, to the circumstances, which according to Art. 91 Criminal Procedure Code of Ukraine are subject to proof in criminal proceedings. This need should promote not only the further intensification of the preventive activities of the investigator, the prosecutor, but also the strengthening of the rule of law and law in the state. Attention is drawn to the fact that due to the lack of a separate rule in the provisions of the current Criminal Procedure Code of Ukraine on the obligation of the prosecution to prove the reasons and conditions that contributed to the commission of a criminal offense, there was a problem with the implementation of Part 1 of Art. 1 of the Criminal Code of Ukraine, according to which one of the main tasks is to prevent crime. The comparison of the provisions of the current Criminal Procedural Code ofUkraine with the Criminal Procedure Code ofUkraine in I960 on the question of the form of prevention of a criminal offense has been formulated. The issue of amending the current criminal procedural legislation ofUkraine has been formulated.

В статье исследовано общее направление профилактической и предохранительной деятельности следователя во время проведения досудебного расследования. Сопоставлено положения действующего УПК Украины и УПК Украины I960 г. по вопросам о формах предотвращения уголовных правонарушений. Сформулирован вопрос о внесении изменений в действующее уголовное процессуальное законодательство Украины.
Кочура, О. О. Запобіжна та профілактична діяльність слідчого під час проведення досудового розслідування як напрями удосконалення чинного КПК України/ О. О. Кочура, Р. М.Балац // Науковий вісник Херсонського державного університету. Сер. : Юридичні науки. – 2018. – Вип. 5. – С. 93-96.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; кримінальне провадження; досудове розслідування; слідчий; запобігання кримінальним правопорушенням; запобіжна діяльність слідчого; причини й умови, що сприяли вчиненню кримінального правопорушення; criminal proceedings; pre-trial investigation; investigator; prevention of criminal offenses; preventive activities of the investigator; reasons and conditions conducive to committing a criminal offense; уголовное производство; досудебное расследование; следователь; предотвращение уголовных правонарушений; предохранительная деятельность следователя; причины и условия, которые способствовали совершению уголовного правонарушения